Physical determinants of overhand service performance among male junior high school students - Miftahul Rizqa; Ridho Bahtra; Sepriadi Sepriadi; Wilda Welis (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the direct and indirect effects of arm muscle strength, hand–eye coordination, and flexibility on overhand service performance among male volleyball players at MTsN 3 Pesisir Selatan. A quantitative correlational design employing path analysis was conducted involving 30 male volleyball players selected through total sampling. Arm muscle strength, hand–eye coordination, flexibility, and overhand service performance were assessed using standardized field tests. The data were analyzed using descriptive statistics and path analysis. Arm muscle strength showed the strongest direct effect on overhand service performance (β = 0.531; 28%), followed by hand–eye coordination (β = 0.295; 9%) and flexibility (β = 0.172; 3%). Flexibility also mediated the relationships between arm muscle strength, hand–eye coordination, and service performance. Collectively, these variables explained 97.7% of the variance in overhand service ability (R² = 0.977). Arm muscle strength, hand–eye coordination, and flexibility are significant determinants of overhand service performance. Therefore, integrated training emphasizing these physical components is recommended to optimize service performance in adolescent volleyball players.